CALISTHENICS EXERCISES TO INTERVENE IN OBESITY AND DIABETES IN MIDDLE-AGED PEOPLE - Kong,Ningning (2022)
ABSTRACT Introduction: There is an annual increase in type 2 diabetes (T2DM) incidence in middle-aged people. Aerobic exercise is known to influence glucose metabolic pathways positively. Few studies concerning calisthenic aerobic exercise and its influence on elderly patients with T2DM. Objective: To measure the therapeutic effect of calisthenic exercise in obese Middle-aged people with T2DM. Methods: A total of 86 patients with T2DM were selected from the physical examination of employees of the same unit. They were randomly divided into the exercise group and the control group. The exercise intervention lasted for 16 weeks, with sessions held 3-5 times per week, varying from 60 to 90 minutes per session. The markers evaluated were defined according to the literature and statistically verified. Results: After 16 weeks of calisthenic exercise intervention, compared to the control group or before the experiment, we observed significant reductions in variables VFA (visceral fat area), FPG (fasting glucose), Fins (fasting insulin), HOMA-IR (homeostasis model evaluation of insulin resistance), 2hPBG (postprandial two hours glucose) and HbAlc (hemoglobin Alc) of the exercise group were significantly reduced (P<0.01). Conclusion: Calisthenic exercise intervention can reduce the levels of VFA, FPG. FIns, HOMA-HR, 2hPBG and HbAlc in patients with T2DM. It was also found to reduce the visceral fat content of obese elderly patients with T2DM, reducing obesity risks. Level of evidence II; Therapeutic studies - investigation of treatment results.